Implementation of lean tools as waste assessment method in a coil spring manufacturing - Rabiatul Syuhada, Hasan; Muhammed Nafis, Osman Zahid (AIP, 2022)
Lean manufacturing is a systematic methodology to minimize waste while maximizing resource utilization which helps business become more effective and competitive in the marketplace. Lean manufacturing is about the enthusiasm for waste elimination. Any business can remain competitive if it is flexible enough to continuously and systematically improve its manufacturing process by eliminating waste, optimize processes, and cut unnecessary cost. This review aims to discuss a wastage assessment method that has been used to implement lean manufacturing across all manufacturing sectors like automotive, electronics, plastic, textile, food, dairy, even services. Specifically, it investigates which are the most common lean tools to be utilized and which has an impact on an organization’s performance. In this context, waste is defined as unproductive manufacturing practices by which it does not add value to the product or services and customers are not willing to pay. A comparison of lean tools was made and discussed to analyse the effectiveness of the tool’s performance.